For Sustainable Economic Growth that Seeks Improving Environmental Quality An Empirical Analysis Applied To Morocco Algeria Tunisia and Egypt (Global Journal of Human-Social Science, 2018)
This paper tries to examine the link between economic growth and environmental damage in Morocco, Algeria, Tunisia, and Egypt, denoted MATE. The main objective for these countries in the coming years is to improve economic growth, which is necessary in response to the increasing demand of their populations, the improvement of the life's quality of their citizens, and to meet the environmental challenges they face. For that, two steps are followed to investigate the relationship between economic growth and environmental damage. In the first step, a basic Environ-mental Kuznets Curve (EKC) equation for each country over the period 1970-2010 is tested to measure the effect of economic growth on environmental quality and to determinate the possibility of the existence of an EKC. In the second step, a few variables are introduced in the basic EKC equation (model tested in the first step) such as economic openness indicator, enrollment rate, and urbanization rate. The purpose is to measure the possible of influence of these variables (included economic growth) on the environmental damage, and to determinate also the possibility of the existence of an EKC. The results of both models show that the relationship between economic growth and environment is complex and ambiguous.
Keywords: economic; growth environmental; degradation; EKC